2019
DOI: 10.5812/jcrps.97880
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training on Fibrinogen and Viscosity of Plasma: Comparing Endurance Continuous, Circuit Resistance and High Intensity Interval Trainings in Young Obese Men

Abstract: Objectives: The aim of the present research was to investigate the effects of endurance continuous training (ECT), circuit resistance training (CRT), high intensity interval training (HIT) on fibrinogen and plasma viscosity in young obese men. Methods: For this purpose, 44 young obese men voluntarily participated in the study, and randomly assigned into (CRT; n = 11), (ECT; n = 11), and (HIT; n = 11), and control group (Con; n = 11). ECT was done with 70% VO2max, while, HIT performed with 6 set of 3 minutes ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The above--mentioned risk factors are accompanied by endothelial dysfunction [3,31]. In addition, the blood viscosity rises, increasing the time of blood stagnation, atherogenic particles are deposited, which penetrate the inner membrane, and consequently, atherosclerotic plaques are formed [32]. Factors that reduce the level of fibrinogen and improve the rheological properties of blood include statins, fibrates, allopurinol, heparin, acetylsalicylic acid, and exercise [23].…”
Section: Fibrinogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The above--mentioned risk factors are accompanied by endothelial dysfunction [3,31]. In addition, the blood viscosity rises, increasing the time of blood stagnation, atherogenic particles are deposited, which penetrate the inner membrane, and consequently, atherosclerotic plaques are formed [32]. Factors that reduce the level of fibrinogen and improve the rheological properties of blood include statins, fibrates, allopurinol, heparin, acetylsalicylic acid, and exercise [23].…”
Section: Fibrinogenmentioning
confidence: 99%
“…Changes in blood viscosity have been described in cardiovascular diseases such as myocardial infarction, ischemic heart disease, hyperlipoproteinemia, and atherosclerosis [32,35]. Circulatory system disorders and changes in the hemorrhagic parameters may occur [18,26,44].…”
Section: Clinical Significancementioning
confidence: 99%
“…A study conducted by Ribeiro Costa et al demonstrated that an eight-week period of high-intensity interval training (HIIT) did not have any significant impact on omentin and vaspin levels in obese rats [ 274 ]. Asadi et al (2019) compared the effect of 12 weeks aerobic exercise (70% VO 2 max), resistance exercise (11 exercises at 20% 1RM), and HIIT (six three-minute sets of running at 90% of VO 2 max) on omentin and vaspin in obese young men, finding no significant difference between the different training programmes [ 275 ] (Table 2 ; Fig. 2 ).…”
Section: Acute and Chronic Exercise Effects On Exerkinesmentioning
confidence: 99%